School of Diplomatic English - D. A. Kryachkov (Vestnik MGIMO-Universiteta)
Chair of English Language № 1 considers itself the successor of the English Language Chair, established at the Faculty of International Relations at the Moscow State University during the World War II. After the Faculty was reformed into MGIMO the Department of English Language began to grow rapidly. Members of the chair develop textbooks and teaching materials designed to provide competence-based approach in the education in field of international affairs, the development of the professional proficiency in English, which are necessary for future participants of our foreign policy. To date, the chair staff consists of 60 professionals, including 26 PhDs. Teachers of the department also conduct research and take part in educational conferences both in Russia and abroad, including those devoted to the professional foreign language communication. Members of the chair also publish scientific articles in this field.